Impact of reversible inhibitor binding to protein Arginine Deiminase Type 4 (PAD4): Molecular Dynamics Simulation and Mmpbsa Calculation - Zainal Fithri, Helmi Husaini; Ibrahim, Zalikha; Ali, Ernie Zuraida (2022)
PAD4 catalyses the conversion of peptidylarginine into peptidylcitrulline. Overexpression of PAD4 and the peptidylcitrulline products have been reported in various diseases including rheumatoid arthritis and cancers. GSK199 is the first PAD4 selective reversible inhibitor discovered. The impact of GSK199 binding on PAD4 stability and flexibility, however, is poorly understood. Here, the impact of GSK199 binding towards PAD4 stability and flexibility is investigated via molecular dynamics simulation, followed by molecular mechanics generalised Poisson-Boltzmann surface area (MMPBSA) calculation. A simulation of inactive control, GSK106 with PAD4 was also conducted for comparison. The atomic deviation plot shows both simulations were stable throughout 100 ns. The atomic fluctuation at the N-terminal domain in the PAD4-GSK199 complex was significantly higher compared to in the PAD4-GSK106 complex, indicating that the PAD4 inhibition gives impact mainly at the N-terminal domain. The MMPBSA analysis shows a marked difference in binding free energies, with -60.95 kJ/mol in the PAD-GSK199 complex and -30.92 kJ/mol in the PAD4-GSK106 complex. Further analysis revealed that the GSK199’s binding to PAD4 is assisted by 5 hydrogen bonds, whereas the GSK106’s binding is aided by 3 hydrogen bonds. Furthermore, GSK106 was found to be in close proximity (1.9 Å) to the backbone of ASN585, which contributed to the binding free energy. The findings from this study provide valuable insight for rational design of other PAD4 reversible inhibitors.